2008
DOI: 10.1002/jgm.1220
|View full text |Cite
|
Sign up to set email alerts
|

Clinical‐grade preparation of human natural regulatory T‐cells encoding the thymidine kinase suicide gene as a safety gene

Abstract: The efficient procedure reported here for the preparation of nTreg, whose safety has been ensured, is now applicable for further clinical trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 45 publications
1
23
0
Order By: Relevance
“…(ii) control GVHD (Cohen, Boyer et al 1997;Cohen, Saron et al 2000;Cohen, Boyer et al 2001). Clinical protocol associated with injection of regulatory T cells expressing the TK gene as a safety gene to control GVHD are under assessment (Guillot-Delost, Cherai et al 2008). Applied upon an allograft this treatment allows delayed rejection (skin graft) or tolerance of the graft (vascularized heart allograft) (Braunberger, Cohen et al 2000;Braunberger, RaynalRaschilas et al 2000;Thomas-Vaslin, Bellier et al 2000).…”
Section: Specific Transient Depletion Of Dividing T Cells To Control mentioning
confidence: 99%
“…(ii) control GVHD (Cohen, Boyer et al 1997;Cohen, Saron et al 2000;Cohen, Boyer et al 2001). Clinical protocol associated with injection of regulatory T cells expressing the TK gene as a safety gene to control GVHD are under assessment (Guillot-Delost, Cherai et al 2008). Applied upon an allograft this treatment allows delayed rejection (skin graft) or tolerance of the graft (vascularized heart allograft) (Braunberger, Cohen et al 2000;Braunberger, RaynalRaschilas et al 2000;Thomas-Vaslin, Bellier et al 2000).…”
Section: Specific Transient Depletion Of Dividing T Cells To Control mentioning
confidence: 99%
“…5 Protocols for the expansion of human FOXP3 + Treg cells performed under conditions of good manufacturing practice (GMP) have been shown to be feasible. 3,[6][7][8] Importantly, these culture conditions are also highly advantageous for the expansion of effector CD25 + T cells, which may contaminate the starting peripheral FOXP3 + Treg cells. This obstacle can be bypassed by: (i) the use of cord blood Treg cells, 4 (ii) isolation of very pure peripheral Treg cells through flow-based cell sorters 3,9,10 or (iii) the addition of rapamycin to the culture, which preferentially inhibits proliferation of effector T cells while sparing Treg cells.…”
Section: Introductionmentioning
confidence: 99%
“…These results are not novel because we have previously demonstrated that rapamycin selectively blocks the in vitro expansion of human CD4 + CD25 − conventional T cells, while allowing nTreg growth [3,5]. In addition, the finding that rapamycin-expanded nTreg retain a broad T cell receptor (TCR) repertoire shown by Guillot-Delost et al [1] was also reported in our previous publications [5,8]. Finally, the authors state that 'Although several strategies that combined stimulation of TCR, CD28 and IL-2R have been developed for long-term culture and polyclonal expansion of nTreg in recent years [9][10][11], none of them were efficient enough to generate large numbers of nTreg'.…”
mentioning
confidence: 69%